Effect of chemical treatment on tensile strength and surface roughness of 3D-printed ABS using the FDM process. Issue 3 (3rd July 2018) - Jayanth, N.; Senthil, P.; Prakash, C.
ABSTRACT: Fused deposition modelling (FDM) is one of the most commonly used additive manufacturing processes because of its environment-friendly nature and cost-effectiveness. However, it suffers badly from low surface quality due to a larger layer resolution. The surface finish of FDM parts can be enhanced by post chemical treatment using various solvents. The chemical treatment reduces the surface roughness by dissolving the external surfaces of 3D-printed samples. Chemical treatment is an easy, fast and economical technique. In the present investigation, the effect of chemical treatment on surface roughness and tensile strength of acrylonitrile butadiene styrene (ABS) parts made using the FDM process is investigated using two chemicals, namely acetone and 1, 2 dichloroethane. The post chemical treatment dramatically improves the surface finish and dimensional accuracy of ABS specimens. But chemical treatment results in the reduction of the tensile strength. Better tensile strength is obtained while using acetone solvent and a better surface finish is obtained using dichloroethane.